2023
DOI: 10.3390/membranes13010100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Performance of Semi-Refined Kappa Carrageenan-Based Film Incorporating Cassava Starch

Abstract: This paper reports the incorporation of cassava starch (CS) at various concentrations into a previously developed ZnO/SiO2-semi-refined kappa carrageenan-based film (SRκC) bionanocomposite and evaluates its performance as minced chicken edible packaging. The incorporation of CS into SRκC-based films aims to provide multifunctional food packaging with enhanced surface morphology, thickness, mechanical properties, and transparency. The effect of the incorporation of various mixing ratios of CS and SRκC (CS:SRκC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Panatarani and coworkers protected minced chicken with semi-refined kappa carrageenan-based film mixed with cassava starch and ZnO and SiO 2 nanoparticles. The authors reported that the film exhibited improved water barrier and mechanical and optical properties while extending the shelf-life of minced chicken for up to 6 days [165]. Kim et al synthesized a biodegradable carrageenan-based functional nanocomposite film with silver nanoparticles that was made using pine needle extract.…”
Section: Carrageenanmentioning
confidence: 99%
“…Panatarani and coworkers protected minced chicken with semi-refined kappa carrageenan-based film mixed with cassava starch and ZnO and SiO 2 nanoparticles. The authors reported that the film exhibited improved water barrier and mechanical and optical properties while extending the shelf-life of minced chicken for up to 6 days [165]. Kim et al synthesized a biodegradable carrageenan-based functional nanocomposite film with silver nanoparticles that was made using pine needle extract.…”
Section: Carrageenanmentioning
confidence: 99%
“…Additionally, sponges have a higher drug loading capability than thin films because of their high surface to volume ratio and porous nature (Ossama et al., 2021 ). Biopolymer-based sponges have additional advantages such as abundance, biodegradability, safety, biocompatibility, and cost-effectiveness (Rudhziah et al., 2019 ; Yanteng Zhao et al., 2019 ; Panatarani et al., 2023 ; Peleg-Evron et al., 2023 ). Amongst these biopolymers, seaweed kappa-carrageenan (κc) is an anionic polymer and consists of linear-sulfated polysaccharides of D-galactose and 3, 6-anhydro-D-galactose ( Figure 1(a) ) (Keshk et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%